Nascent Entrepreneurship Training From The Perspective Of Startup Pathways - Retnowati, Elais; Sutisna, Anan; Lestari, Retno Dwi (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2023)
Entrepreneurship training faces various challenges that affect the success of launching startups. This research  analyzes the implementation of entrepreneurship training in terms of startup pathways: create, system, and grow. The research method used Participatory Action Research (PAR). The study was conducted in Sirnajaya Village, Bogor from October 2022-November 2023. The population was Tourism Awareness Group and the sampling techniques used purposive sampling. The findings indicate that the entrepreneurship training design significantly contributed to the launch of startup ventures. Obstacle in one startup pathway will impact subsequent pathways. This condition persists, even affecting participants who have management competence in business growth strategies. The research also emphasizes the importance of integrating each stage with empowering principles. This study contributes to the entrepreneurship training design that consider startup pathways, empowerment, and entrepreneurial competencies.